Efforts and Support of Digital Literacy Program Development by Student Real Work Lecture Program to Improve the Quality of Human Resources of Digital Technology Use - Dhianawaty, Diah; Dwiwina, Resti Gradia; Achadiyani (Innovare Journal of Education, 2023)
The impact of the COVID-19 outbreak has caused learning activities to be carried out by utilizing information technology. The ability to use information technology during the COVID-19 era was being developed to increase people’s ability to utilize digital technology through digital literacy programs. The digital literacy program socialization was carried out in the following steps. Initially, the team members received work direction from the Directorate of Informatics Empowerment team of the Ministry of Communication and Informatics, Republic of Indonesia. Then, the team members met the Village Head and his staff to introduce the digital literacy program and ask for permission and support for this program. Afterward, the team member met the heads of the Youth organization and Junior high school and asked permission to socialize digital literacy with their members and the students. The digital literacy program was socialized to two groups: the young community in Mekarwangi village, members of Youth organizations, and Junior high school students. The total number of each group was 19 participants from Youth organization members and 191 participants from Junior high school students. All participants were educated on four pillars: digital ethics, digital safety, digital skills, and digital culture. The total number of participants was 210, have improved their skills and knowledge. They should care about digital skills, security, ethics, and culture. It was expected that in the future, participants would be able to implement the four main pillars and become qualified users of digital technology.